AN ANALYSIS OF THE USE OF HEDGES BY YOUNG CHILDREN - Uli Alfan Hasani; Dyah Indah Nugraheni; Muhammad Fikar Fauzi; Rolisda Yosintha (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Children tend to have simple pronunciation and language compared to adults. However, children will also experience language development according to their age such as Noah Ritter, who was five years old when interviewed by television stations until invited to the Ellen Show two years letter when Noah was seven years old. Noah Ritter is also nicknamed